Desenvolvimento de um adesivo nanomodificado por grafeno - Almir Silva Neto (2011)
A low viscosity adhesive has been developed to be applied to large areas. The AR300 epoxy system was nanomodified by graphene nanoparticles and used as an adhesive - AR300G. The aparent shear strength of single-lap joints was measured and results were close to comercial structural adhesives. An increase on load capacity of 57,7% was noticed with the addition of 2wt% of graphene. AR300s low viscosity makes this adhesive a good option for large area applications, e.g., oil pipe repairs, boat hull manufacturing, aircraft fuselage assemblage andsandwich structures. Furthermore, the usage of high shear and ultrasonic mixing procedures was able due to low viscosity of AR300G. X-ray diffraction signatures indicated formation of nanostructures with average size of 17 nm and basal spacing of 0.34 nm. With nanoindentation s results it was possible to measure the Young modulus of the adhesive with and without nanoparticles. An increase on stiffness ( 22,3%) was detected by nanoindentantion for the2wt% AR300G.